Metabolic Syndrome-A Detrimental Prognostic Predictor in Middle Aged Individuals with Heart Failure-A Study in South Indians - B.B.Abdullah; A.Satyasrinivas; B.S.Patil; S.M.Ashraf; S.Ali (Al Ameen Journal of Medical Sciences, 2012)
Background: Prognosis of heart failure in metabolic syndrome is not well established because it represents a heterogenous spectrum of myocardial disorders that each may progress at different rates. The present study determines the prognosis of heart failure in metabolic syndrome of middle aged individuals in terms of mortality and morbidity. Material and Methods: 100 patients studied (60 with metabolic syndrome, 40 without metabolic syndrome) with moderate – severe symptoms of heart failure associated with an ejection fraction equal or less than 40% and QRS duration of 130 sec or more were randomly selected. These patients were treated with conventional therapy for heart failure and monitored for 24 weeks. Primary end points were NYHA class, distance walked in 6 minutes, and secondary end points were LVEF, LVEDD, SPAP and QRS duration. Result: As compared with the patients without metabolic syndrome, metabolic syndrome patients experienced decrease in the distance walked in 6 minutes (336.40 ± 16.0 Vs 285.35 ± 3.30), functional NYHA class improvement (75% Vs 33.3%), LVEF (35.22 ± 1.7 Vs 31.63 ± 2.74), In addition, metabolic syndrome group, required more hospitalizations and intravenous medications (50% Vs 10%). Conclusion: Moderate to severe heart failure patients with metabolic syndrome result in less significant improvement in heart failure when compared to heart failure without metabolic syndrome patients.